Beyond Clicks: Enhancing Live Shopping Experiences with Visual Appeal, Social Support, and Purchase Intent Sparks - Batara, Lisa Charisa; Suryandari, Retno Tanding; Suryanadi, Pram; Sugiarto, Catur (APMBA (Asia Pacific Management and Business Application), 2024)
This research delves into the intricate dynamics of consumer behavior on social commerce platforms, emphasizing the connections between visual appeal, customer involvement, hedonic value, social support, and buy intention. A positive link between visual appeal and hedonic value (t = 3.980, p < 0.001) is revealed by our analysis of 249 respondents' data using SmartPLS 3, highlighting the critical role that visually appealing information plays in piquing consumers' interest and encouraging participation. Furthermore, we emphasize the role that social support plays in determining customer engagement (t = 5.067, p < 0.001) and hedonic value (t = 3.134, p = 0.002), demonstrating the necessity of establishing social ties in online shopping settings. Our study found that hedonic value had a substantial impact on purchase intention (t = 7.672, p < 0.001), indicating that emotional fulfillment is an important factor in consumer decision-making. We also find a strong association between customer engagement and purchase intention (t = 3.372, p = 0.001), indicating that actively engaging customers in brand experiences enhances their likelihood of making a purchase.